Structural performance of poultry eggshell derived hydroxyapatite based high density polyethylene bio-composites. Issue 10 (October 2019) - Oladele, Isiaka Oluwole; Agbabiaka, Okikiola Ganiu; Adediran, Adeolu Adesoji; Akinwekomi, Akeem Damilola; Balogun, Augustine Olamilekan
Abstract: In this research, hydroxyapatite (HAp) was synthesized from chicken eggshell waste by hydrothermal method for the development of bio-composite material suitable for biomedical implant. However, since environmental influences on natural materials are unique for different geographical locations in the world, the use of agro wastes from these locations need to be investigated. This work provides the detail results of the potentials of eggshell as HAp source. High-density polyethylene (HDPE)/HAp composites were developed by random dispersion of Hap (10, 20, 30 and 40 wt.%) in HDPE matrix, and were designated as HAC10, HAC20, HAC30, and HAC40. The HAp-filled HDPE composites were developed by a hot compression moulding process. The samples were subjected to tensile, flexural, impact, fracture toughness and wear tests according to ASTM standards in order to establish their structural performance as an implant material. Furthermore, the samples were also tested for hydrophilicity using tap water and simulated body fluid (SBF). X-ray diffraction analysis showed strong peaks of hydroxyapatite phase which established that the influence of the selected processing conditions on the poultry eggshell as a natural source for the biomedical application was suitable for the synthesis of high-quality hydroxyapatite. The mechanical properties of the developed composites were enhanced to the level of the required properties expected of an implant material compared to the control sample except for impact strength. Water absorption characteristics of the developed composite samples also displayed expected behaviour in SBF solution than in tap water thereby promoting the material as a good implant material. From the results, the sample with 40 wt.% HAp possess the highest values in the mechanical properties examined while sample from 20 wt.% had the best fracture toughness. The results revealed that these waste eggshells could be successfully converted into useful biocompatible HAp particles needed for the enhancement of the mechanical properties of polymer composites to meet the structural challenges of bio-composites.